Lutra provoeax Thomas 1908 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Lutra provoeax Thomas, 1908. Ann. Mag. Nat. Hist., ser. 1:391. TYPE LOCALITY: Argentina, S. of Lake Nahuel Huapi. DISTRIBUTION: Patagonia (C. and S. Chile; W. Argentina). PROTECTED STATUS: CITES - Appendix I and U.S. ESA - Endangered. ISIS NUMBER: 5301412004023004001 as Lontra provoeax. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Carnivora, pp. 244-289 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 258, DOI: 10.5281/zenodo.7352980